Pathway analysis of nursing interns’ professional benefit perception and influencing factors: a cross-sectional study - Su, Mei; Hu, Ying; Sun, Jiaxin; Chang, Wenzhong; Li, Yaru; Tang, Peijuan; Cui, Yajuan; Ma, Yujia; Wang, Yanting; Zhang, Fengxian; Wang, Jia; Hu, Yuchong (Frontiers in Medicine, 2025)
AimThis study aims to examine the current professional benefit perception among nursing interns and explore their interactions with perspective taking, compassion satisfaction, and secondary traumatic stress.BackgroundThe professional benefit perception is a crucial determinant in the career decisions of nursing interns. Understanding the pathways through which various factors influence this perception can inform the development of targeted intervention strategies. Such strategies are essential for preventing the attrition of nursing professionals and addressing the shortage of nursing human resources.DesignA cross-sectional design.MethodsCross-sectional data were obtained from Inner Mongolia, China. To examine the influencing factors and pathways, multiple linear regression and the Hayes PROCESS macro were employed.ResultsThe study encompassed 427 nursing interns, whose perception of professional benefits was assessed at a moderate to high level, with a mean score of 4.29 ± 0.61. This perception was significantly affected by perspective taking (t = 3.990, p < 0.001), compassion satisfaction (t = 9.073, p < 0.001), secondary traumatic stress (t = −3.918, p < 0.001), overall satisfaction, and academic performance. Compassion satisfaction served as a mediator in the relationship between perspective taking and professional benefit perception, with a mediation effect value of 0.167, constituting 62.78% of the total effect. Furthermore, secondary traumatic stress moderated the relationship between compassion satisfaction and professional benefit perception, with an interaction effect value of β = 0.067 (p < 0.05).ConclusionThe professional benefit perception among nursing interns is shaped by a multitude of factors. Consequently, clinical educators should consider integrating these multidimensional factors to develop precise intervention programs aimed at enhancing professional identity and supporting the development of nursing talent.